Allele frequencies for STR loci in a Sicilian population: Genetic prevalence and disequilibrium - Ciuna, I.; Guarnaccia, M.; Ginestra, E.; Agodi, A.; Piscitello, D.; Spitaleri, S.; Marcì, G.; Paravizzini, G.; Trapani, C.; Travali, S.; Saravo, L. (International Congress series, 2006)
The aim of our work was to study the allelic frequencies and distribution within the 15 forensic STR loci in a group of 440 unrelated Sicilian subjects. Afterwards we have evaluated the genetic equilibrium among the most recurrent allele loci and have compared our data to those already published by other authors referring to different populations.